The effectiveness of a training program based on the components of moral intelligence in developing academic engagement and decreasing the level of Cyberbullying among high school students - Abdellatif, Mohamed Sayed Mohamed (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the effectiveness of a training program based on the components of moral intelligence in developing academic engagement and reducing the level of cyberbullying among high school students. The experimental study group consisted of (32) students. The researcher applied the following tools: (the training program based on the components of moral intelligence, academic engagement scale, cyberbullying scale). The researcher used the quasi experimental method. The researcher used the "T" test to statistically treat the data and verify the hypotheses. the researcher concluded several results, including: There were significant differences between the average degrees of the experimental study group on two scales (academic engagement and its dimensions, and cyberbullying and its dimensions) in the pre and post measurements toward post-measurement. There were no significance differences between average degrees of the experimental study group on two scales (academic engagement and its dimensions, and cyberbullying and its dimensions) in the post and follow up measurements (after a month). The researcher provided a thorough discussion of the study variables, academic integration, cyberbullying and the training program based on moral intelligence in the current study. The researcher also presented some recommendations and suggested research.